Elderly people\'s perceptions of the facilitators of abuse: A thematic analysis - Masoomeh Adib; Maryam Esmaeili; Masoumeh Zakerimoghadam; Nahid Dehghan Nayeri (Tehran University of Medical Sciences, 2021)
Background & Aim: With the increasing phenomenon of elder abuse in todaychr('39')s societies, understanding the facilitating and inhibiting factors related to abuse seems necessary. The purpose of this study was to explain the facilitators of elder abuse in Iranian society. Methods & Materials: This is a qualitative study that used a thematic analysis approach to collect and analyze data in order to explain the elderly's perceptions of the facilitators of abuse. In this study, 20 elderly people in the community were selected by purposeful sampling. The data were collected by in-depth, semi-structured and face-to-face individual interviews. The Braun and Clark's thematic analysis was used to analyze the data. Results: The results of data analysis led to the identification of three themes including role modeling, evacuation of failures, and cultural-familial context of the society. The third theme had three sub-themes intergenerational gap, parenting style and society's indifference. Conclusion: Abuse is the result of a combination of causes and factors. The elderly' experiences suggest that abuse goes beyond a personal matter and is rooted in cultural, social, and economic practices. Today, it is not acceptance of each other and disregard for the expectations of the other party that gives rise many contradictions and abuses at the family and community level.